Lichen ruber planus in pediatric age and Mycoplasma pneumoniae. - Boccardi, D.; Nobile, M.; Savalli, F.; Gualandri, L.; Menni, S. (European Journal of Pediatric Dermatology, 2006)
Two cases of lichen ruber planus in pediatric age, a classic and a linear form, were reported. In both cases, the clinical diagnosis was confirmed by the histologic examination. The children were given antibiotic therapy with clarithromycin oral suspension 15mg/kg per day for 15 days and local emollients, because of the finding of IgM anti- Mycoplasma pneumoniae, while the remaining ruotine laboratory data were normal. After a month from the beginning of the therapy, the lesions flattened, leaving residual pigmentation, except for the linearly arranged lesions, still modestly observable after two months from the administration of clarithromycin. Mycoplasma pneumoniae is responsible usually for respiratory problems. It is only very rarely involved in disorders of the nervous system, heart and skin. The possible role of this micro-organism in the pathogenesis of lichen ruber planus was discussed.